Pneumonia pada Anak - Agnes S. Rahayu (Jurnal Biologi Papua, 2011)
Pneumonia is the leading cause of death among children worldwide. It causes more death than any other diseases, even AIDS and malaria. One of five children under the age of five died of pneumonia and over two million children around the world died of it each year.Pneumonia generally caused by infection, lungs become inflamed and congested, reducing oxygen exchangeandleading to cough and breathlessness.. In developed countries, deaths from pneumonia have been reduced by improvements in living conditions, air quality and nutrition. In the developing world today, many deaths from pneumonia are also preventable by immunization.Key words: children, pneumonia, immunization.